Teaching kinetic energy as an observable quantity. (16th April 2019) - Hartmann, Bruno; Priemer, Burkhard
Abstract: In this paper we present a novel approach to teach kinetic energy as an observable and measurable concept. The fundamental principles have been outlined for gravitational potential energy in an earlier work, that we extend here. By accelerating or decelerating bodies with springs we begin, in a first step, with a direct comparison method for kinetic energies. A second step addresses the quantification of kinetic energy by introducing reference units. Third, we construct a mechanical calorimeter that generates these countable energy portions. And finally, in a fourth step, a quantitative description leads to the fundamental equation, that relates kinetic energy to velocity and mass. We highlight the concept by giving examples that were used and evaluated in high school physics classes.